2021
DOI: 10.1111/idh.12502
|View full text |Cite
|
Sign up to set email alerts
|

Oral health awareness, attitude towards dental treatment, fear of infection and economic impact during COVID‐19 pandemic in the Middle East

Abstract: In December 2019, a considerable number of patients were diagnosed with atypical pneumonia with unknown cause in the Wuhan city, China. Later, in January 2020, the Chinese Centre for Disease Control and Prevention revealed the causality to be a new member of coronaviruses named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). 1 Infection with this virus (termed as COVID-19) is characterized by high person-to-person transmission rates, representing a serious

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
1
16
0
5
Order By: Relevance
“…Twenty-four studies focused on patients receiving general dental treatment [ 76 , 90 , 95 , 98 , 100 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 117 , 119 , 120 , 123 , 124 , 126 , 129 , 130 , 132 , 133 , 134 ], ten on patients under orthodontic treatment [ 96 , 102 , 104 , 105 , 116 , 118 , 125 , 128 , 136 , 137 ], six on pediatric patients [ 97 , 99 , 101 , 103 , 107 , 122 ], two on patients with temporomandibular disorders [ 106 , 135 ], one on patients under endodontic treatment [ 121 ], one on prosthodontic patients [ 131 ], and one on patients undergoing oral surgery [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four studies focused on patients receiving general dental treatment [ 76 , 90 , 95 , 98 , 100 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 117 , 119 , 120 , 123 , 124 , 126 , 129 , 130 , 132 , 133 , 134 ], ten on patients under orthodontic treatment [ 96 , 102 , 104 , 105 , 116 , 118 , 125 , 128 , 136 , 137 ], six on pediatric patients [ 97 , 99 , 101 , 103 , 107 , 122 ], two on patients with temporomandibular disorders [ 106 , 135 ], one on patients under endodontic treatment [ 121 ], one on prosthodontic patients [ 131 ], and one on patients undergoing oral surgery [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…), the main study variable analyzed was the fear of visiting the dentist during the pandemic (n = 11), reaching up to 63.6% of these patients [ 115 ]. Various studies [ 95 , 100 , 110 , 111 , 112 , 113 , 115 ] found a greater reluctance to seek dental treatment and a more marked tendency to postpone appointments among female patients and among over 60-year-olds who had a systemic disease. The delay in dental care, mainly due to restrictive measures, was associated with depression in adults of middle age (Odds Ratio (OR): 2.05, 95% confidence interval (CI): 1.04–4.03) and in those over 65 years old (OR: 3.08, 95% CI: 1.07–8.87) [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the pandemic began, research has focused on both minimizing aerosols in dental practices and the optimal allocation of rooms where aerosol-generating procedures can be safely carried out [ 15 , 16 , 17 ]. The results of this study highlight the fact that pain-relieving procedures, such as restorative care, oral surgery, and endodontics quickly bounced back to pre-pandemic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Data are emerging from around the world showing that the initial reluctance of individuals to seek dental treatment during the pandemic has been replaced by differing access to dental care [ 3 , 11 , 12 , 13 ]. While there have been some attempts to analyze data from multiple centers [ 14 , 15 , 16 ], there is little longitudinal data from a large public hospital. Newer variants of the virus and increased transmissibility mean the world has seen the pandemic slowly start to show features of an endemic.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies reported that there was a negative impact on the attitudes of individuals towards oral healthcare in the future [54,58,62,68,77,95,99,100,106,[111][112][113][114][115][116][117][118]. In one study, 41% of patients reported that their greatest concern for oral health services in the future was the delay in completion of their dental treatment [95].…”
Section: Attitudes Towards Seeking Oral Healthcare In the Futurementioning
confidence: 99%